Common network effect-patterns after monoamine reuptake inhibition in dissociated hippocampus cultures - Trepl, Julia; Dahlmanns, Marc; Kornhuber, Johannes; Groemer, Teja W.; Dahlmanns, Jana (Journal of Neural Transmission, 2022)
The pharmacological treatment of major depressive disorder with currently available antidepressant drugs is still unsatisfying as response to medication is delayed and in some patients even non-existent. To understand complex psychiatric diseases such as major depressive disorder and their treatment, research focus is shifting from investigating single neurons towards a view of the entire functional and effective neuronal network, because alterations on single synapses through antidepressant drugs may translate to alterations in the entire network. Here, we examined the effects of monoamine reuptake inhibitors on in vitro hippocampal network dynamics using calcium fluorescence imaging and analyzing the data with means of graph theoretical parameters. Hypothesizing that monoamine reuptake inhibitors operate through changes of effective connectivity on micro-scale neuronal networks, we measured the effects of the selective monoamine reuptake inhibitors GBR-12783, Sertraline, Venlafaxine, and Amitriptyline on neuronal networks. We identified a common pattern of effects of the different tested monoamine reuptake inhibitors. After treatment with GBR-12783, Sertraline, and Venlafaxine, the connectivity degree, measuring the number of existing connections in the network, was significantly decreased. All tested substances led to networks with more submodules and a reduced global efficiency. No monoamine reuptake inhibitor did affect network-wide firing rate, the characteristic path length, or the network strength. In our study, we found that monoamine reuptake inhibition in neuronal networks in vitro results in a sharpening of the network structure. These alterations could be the basis for the reorganization of a large-scale miswired network in major depressive disorder.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antidepressants; Connectivity; Hippocampal networks; Hippocampus culture; Monoamine reuptake inhibitors

Correction to: Common network effect‑patterns after monoamine reuptake inhibition in dissociated hippocampus cultures (Journal of Neural Transmission, (2022), 129, 3, (261-275), 10.1007/s00702-022-02477-6) - Trepl, Julia; Dahlmanns, Marc; Kornhuber, Johannes; Grömer, Teja Wolfgang; Dahlmanns, Jana (Journal of Neural Transmission, 2022)
The Acknowledgements section was missing from this article and should have read: The present work was performed in (partial) fulfillment of the requirements for obtaining the degree "Dr. med."/"Dr. med. dent. The original article has been corrected.
CRIS-Team Scopus Importer:2022-10-21